Peranan Guru Pendidikan Agama Islam dalam Meningkatkan Kecerdasan Spiritual Peserta didik - Nisa, Chairun; Daivina, Dara (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2023)
The learning objectives that must be achieved by students are not only in the cognitive domain but also in the affective and psychomotor domains. Spiritual intelligence is included in the affective domain that must be mastered by students. Spiritual intelligence can be achieved properly if the teacher carries out his role as well as possible. This study aims to determine the role of the PAI teacher in learning and the efforts made by the PAI teacher to increase the spiritual intelligence of students. This study used a qualitative descriptive approach with data collection techniques using observation, interviews, and documentation. The data sources for this research were PAI teachers and students of SMP Negeri 1 Takengon. The results of the study show that the role of the PAI teacher in increasing the spiritual intelligence of students is as a motivator, mentor, role model, informant, and organizer. Efforts made by PAI teachers are to involve students in routine religious activities, which are part of the madrasa program. Taking turns reading the Koran, reading prayers before studying, praying, reciting the Yasin surah, and praying in congregation, which are carried out regularly. Keywords: Role of Teacher of Islamic Religious Education; Spiritual Intelligence; Religious Activities